2020
DOI: 10.1039/d0ee01607a
|View full text |Cite
|
Sign up to set email alerts
|

K+ modulated K+/vacancy disordered layered oxide for high-rate and high-capacity potassium-ion batteries

Abstract: With high theoretical capacity and applicable operating voltage, layered transition metal oxides are potential cathode for potassium-ion batteries (PIBs). However, K+/vacancy ordered structure in these oxides limits the K+ transport...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
94
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 42 publications
0
94
1
Order By: Relevance
“…Reproduced with permission. [ 48 ] Copyright 2020, The Royal Society of Chemistry. Polyhedral view of the crystal structure of P2‐K 2 Ni 2 TeO 6 along g) the c ‐axis and h) ab plane.…”
Section: Layered Transition Metal Oxidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Reproduced with permission. [ 48 ] Copyright 2020, The Royal Society of Chemistry. Polyhedral view of the crystal structure of P2‐K 2 Ni 2 TeO 6 along g) the c ‐axis and h) ab plane.…”
Section: Layered Transition Metal Oxidesmentioning
confidence: 99%
“…Recently, Xiao et al reported the positive effects of K + /vacancy disordered in layered oxide K 0.7 Mn 0.7 Ni 0.3 O 2 , which exhibits higher discharge voltage, capacity, rate capability, and cycling stability than the K + /vacancy ordered phase (K 0.4 Mn 0.7 Ni 0.3 O 2 ), as shown in Figure 5 d‐f. [ 48 ] The strong K + –K + electrostatic repulsion by increasing the K + content reduces the energy difference of the K + sites, thus breaking the K + /vacancy ordered structure. In addition, the doped transition metal in layered oxides with compatible ionic radius but quite different Fermi levels suppress the M n+ charge ordering, resulting in the K + /vacancy disordering.…”
Section: Layered Transition Metal Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, substantial efforts have been devoted into potassium ion energy storage devices, owing to the abundant potassium resource in crust and comparable energy density. [ 24–26 ] The reduction potential of potassium (−2.93 V vs SHE) gets close to that of lithium (−3.04 V vs SHE), enabling a high operating voltage of potassium ion batteries comparable to lithium ion batteries. [ 27,28 ] Moreover, potassium ions in non‐aqueous electrolyte have a weaker solvation effect and smaller Stokes’ radius than lithium ions, contributing to a higher ion transfer number and conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] In contrast, substantial efforts have been devoted into potassium ion energy storage devices, owing to the abundant potassium resource in crust and comparable energy density. [24][25][26] The reduction potential of potassium (−2.93 V vs SHE) gets close to that of lithium (−3.04 V vs SHE), enabling a high operating voltage of potassium ion batteries comparable to lithium ion batteries. [27,28] To cate for the rapid development of flexible, wearable and implantable microelectronics, the miniaturized and integrated energy storage devices with mechanically robust properties, high voltage, and highly compatible integration are in extreme demand.…”
mentioning
confidence: 99%